Japan's economic dilemma : the institutional origins of prosperity and stagnation - Gao, Bai, 1955- 4 0 16; 5 (New York : Cambridge University Press, 2001)
The Japanese economy, after decades of seemingly unsurpassable competitiveness, experienced a major crisis in the 1990s. The depth of the crisis has been as remarkable as Japan's renowned meteoric success. Economies rise and fall, to be sure; but the magnitude of the Japanese economy's swing within such a short time, and in the absence of major wars, is unprecedented. Observers of Japan are faced with a challenging question: How can one explain Japan's seemingly abrupt reversal from stunning prosperity to dismal stagnation? Bai Gao not only explains the reversion but also goes beyond other analyses to demonstrate how the same economic institutions could produce both stunning international economic success and the subsequent, intractable slump of the 1990s.--BOOK JACKET.
1. Introduction -- 2. Three Theoretical Issues -- 3. The Rise of the Principles of Coordination and Stability -- 4. Coordination, Excessive Competition, and High-Speed Economic Growth -- 5. Stability, Total Employment, and the Welfare Society -- 6. The Roads to the Bubble -- 7. The Struggle of the Welfare Society -- 8. Fighting the Stagnation.
Includes bibliographical references (p. 275-293) and index.
Keywords: 2 -- 0; 6; Financial crises -- Japan. -- 20; Economic conditions -- Japan -- 1989-20; 2